1990
DOI: 10.1002/mma.1670120605
|View full text |Cite
|
Sign up to set email alerts
|

The scattering of electromagnetic waves by a perfectly conducting infinite cylinder

Abstract: We consider the scattering of a plane time-harmonic electromagnetic wave by a perfectly conducting infinite cylinder with axis in the direction k, where k is the unit vector along the z axis. Suppose the incident wave propagates in a direction perpendicular to the cylinder. For a given observation angle 0, let F,(O, a)k be the far-field pattern of the electric field corresponding to an incident wave with direction angle a polarized perpendicular to the z axis and let FN(O;a)k be the far-field pattern of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Indeed, it follows from [S] that this new method for solving the inverse scattering problem fails if the wave number is equal to a Maxwell eigenvalue of the scattering obstacle. In an effort to overcome this defect in a special case, Colton and Monk considered the twodimensional scalar case and showed that if the data were chosen to be a convex linear combination of the electric and magnetic far-field patterns then, if this combination was not degenerate, there was no longer any problem with interior eigenvalues [6]. The purpose of this paper is to extend this result to the full three-dimensional vectorvalued problem.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, it follows from [S] that this new method for solving the inverse scattering problem fails if the wave number is equal to a Maxwell eigenvalue of the scattering obstacle. In an effort to overcome this defect in a special case, Colton and Monk considered the twodimensional scalar case and showed that if the data were chosen to be a convex linear combination of the electric and magnetic far-field patterns then, if this combination was not degenerate, there was no longer any problem with interior eigenvalues [6]. The purpose of this paper is to extend this result to the full three-dimensional vectorvalued problem.…”
Section: Introductionmentioning
confidence: 95%
“…These two problems are to be understood as problems in constrained optimization where h and r are subject to a priori constraints. For details of this procedure for solving the inverse scattering problem in the (scalar) two-dimensional case, including numerical examples, we refer the reader to [6]. It follows from the proof of Theorem 2.3 that the (unconstrained) cost functional of the sum of the above optimization schemes will have zero as its greatest lower bound provided there exists an electric Herglotz field Eh such that (2.22) is approximately satisfied in the space of square-integrable tangential vector fields defined on aD where E, H satisfy (2.21).…”
Section: The Inverse Scattering Problemmentioning
confidence: 99%